FORMATION OF ETHNIC CONSCIOUSNESS OF THE FUTURE PEDAGOGUE IN THE CONDITIONS OF THE EUROPEAN EDUCATIONAL SPACE - VASYLYK, MARYNA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article is devoted to modern approaches of formation of ethnic consciousness of future teachers of primary school in the conditions of the multicultural society and their education as citizens of Europe. Multicultural competence is a factor of a successful professional activity. In the article, the author analyzed the problem of forming of future specialists’ multicultural competence in connection with the globalization processes and integration of Ukrainian higher education in European educational community. The research stresses that formation of students’ outlook, their value orientations, modern social and humanistic thinking in an educational process are important. It is emphasized that the multiculturalness must become an integral part of every national educational system. The multiculturalness is a key principle of making totally new educational system of Ukraine. Respect and acceptance of cultural variety in the society coexistence of dialogues without loss of the national and cultural identity of the representatives of the society leads to its spiritual and cultural enriching. The article is an author's translation of the text published in the Journal of the National Academy of the State Border Guard Service of Ukraine, series: Pedagogics, 5 (2016) (in Ukrainian).